Problems Of Teaching Future Teachers of Fine Arts in Higher Pedagogical Education - Botir Boltabaevich Baimetov; Shohidakhon Odiljonovna Botirova (Genius Journals, 2022)
In the future training of future teachers of fine arts, the student will be able to visualize the basics of visual representation of objects in space, the correct description of the rules of fine arts, the shape, structure, proportions and plasticity of objects.
Keywords: Fine arts; imagination; composition; body